Fossorial snake genus Apostolepis from South America (Serpentes: colubridae: elapomorphinae) - Lema, Thales de (2001)
An update commented list of the snake genus Apostolepis from South America, with keys for identification of the species. They are fossorial snakes that present different coloration according their distribution: (a) 7 to 3 dark stripes coloration, without light nuchal collar (if present, vestigial), with snout not projected beyond jaws - in Amazonian and enclaves within Caatinga domain; (b) 5 dark striped dorsal pattern, snout projected, usually without white nuchal collars — from region of contact between Cerrado and Chaco domains; (c) dorsal pattern coloration uniformly red, with nucho-cervical collars, snout usually projected — in Cerrado with dispersion to Chaco and Caatinga; (d) 2 or none dark stripes dorsally, venter immaculate or with black blotches, snout projecting: (e) an aberrant pattern with oblique black dorsal stripes, without collars, head black and snout projecting — one species in an enclave within Caatinga, with 17 rows of scales instead of 15.